Orchid genera lectotypess - Higgins, Wesley; Alrich, Peggy (Lankesteriana: International Journal on Orchidology, 2011)
The typification of Orchidaceae genera has been disorganized since currently there is not an up to date central database to track these nomenclatural publications. A listing of published generic typifications for Orchidaceae is provided.